An improved voltage compensation approach in a droop-controlled DC power system for the more electric aircraft - Gao, Fei; Bozhko, Serhiy; Asher, Greg; Wheeler, Patrick; Patel, Chintanbai (IEEE, 2015)
This paper proposes an improved voltage regulation method in multi-source based DC electrical power system in the more electric aircraft. The proposed approach, which can be used in terrestrial DC microgrids as well, effectively improves the load sharing accuracy under high droop gain circumstance with consideration of cable impedance. Since no extra communication line and controllers are required, it is easily implemented and also increases the system modularity and reliability. By using the proposed approach the DC transmission losses can be reduced and system stability is not deteriorated for normal and fault scenarios. In this paper optimal droop gain settings are investigated and the selection of individual droop gains as well as the proportional power sharing ratio has been described. Experimental results validate the effectiveness of the proposed method.